A relação entre maternidade e docência no processo de formação e constituição identitária da profissão - Moreira, Evelize Zamone (2024)
The object of study of this research is the trajectory of women who are mothers and teachers and the constitution of their professional identity based on the analysis of their life stories, training path and entry and permanence in the profession. Starting from this object of study, some concerns emerged that motivated and directed the development of this research: considering that the training trajectories are crossed and amalgamated by the life history of the subjects in general and women in specific, the research question turns to how the: does motherhood influence the professionalization trajectory and the constitution of women’s teaching identity? With the questions presented, the general objective was to understand the constituent elements of the teaching identity as a result of the socialization processes of the teacher who is a mother. As specific objectives of the research we list: 1- Analyze the personal trajectory of women - mothers based on markers such as family, schooling and motherhood; 2- Discuss the professionalization trajectory, both with regard to entry into teaching and the influence of motherhood on the professional trajectory. Based on the objectives presented, the research was then developed according to a qualitative approach. The instrument adopted was the sociological portrait based on studies by Lahire (2004) woven from semi-structured interviews covering aspects of family life, school, work, socialization and motherhood. The research subjects were two mother teachers, pedagogues with more than 10 years of teaching experience. We will analyze the constitution of teaching identity, as a result of socialization based on the contributions of Dubar (2005) and Nóvoa (1991; 2000), and the studies of Marcelo (2009) and Imbernón (2011) with regard to training, trajectory, professionalization and teaching identity as social significance. As results it can be stated that the teaching identity is indeed crossed and incorporated as a defining element of trajectories from the intersection with motherhood in the life stories of teachers without, however, meaning a prerequisite for the exercise of teaching